PEMBUATAN MESINPOLES UNTUK PENGRAJIN PERAK DI KOTA GEDE, YOGYAKARTA GUNA MENINGKATKAN KAPASITAS EKSPORT - Widarto, Widarto (Universitas Negeri Yogyakarta, 2003)
The general purpose of this program is to produce Polishing Machines for silver planning and refining work as art craftsmanship commodities. The special purpose of the program are (I) to increase the producing capacity of silver craftsmanship workers' group; and (2) to improve the quality and quantity of production to meet exporters' demand and requirements.Methods constructed to accomplish the mentioned above purpose are (I) to planPolishing Machines model, (2) to design working drawing, (3) to make working schedule, (4) to plan cost, (5) to implement modeling, (6) to test and verify the machines, (7) correcting insufficiencies, (8) to conduct training for industrial operators, (9) to prepare final report.The output of Vucer Program is a Polishing Machines with followingtechnical specifications: (1) Machine dimension = L x W x H : 2200 x 800 x 1000!TIm; (2) Chassis = Profile iron L 32 mrn; (3) Generating power = Electric motor 1 phase, nov, Y2 HP, 1400 rpm; (4) Transmission system = Using pulley without'coupling; (5) Polishing disk revolution =800 rpm; (6) Working hour per day = 6 hours; (7) Production capacity per day = 88 pieces; and (8) Empirical age prediction of machine := ± 8 years. The comparison before and after using the Polishing Machine: (1) Production capacity per day, post-vucer 50 pieces, post-vucer 88 pieces; (2) Grossprofit per day, pre-vucer Rp 50,000, Rp 88,000; (3) Operating cost perday, pre-vucer Rp 15,000, post-vucer. Rp 21,000; (4) Net profit per day, pre-vucer Rp35,000, post-vucer Rp 67,000; (5) Net profit per month, pre-vucer Rp 875,000, postvucer Rp r ,675,000; (6) Profit difference per month = Rp 800,000; (7) Machine price= Rp. 5,000,000; and (8) BEP = 6,25 month. The conclusion of Vucer Program is that: (1) The silver polishing machine is able to improve quality and quantity of product, (2) All machine components function as planned, and even allow for further development, (3) Machine. operation is simple, (4) the performance is good from technical point of view, (5) from economic point of view, it is very feasible for the silver craftsmanship workers. The vacuum cleaner installation is recommended for optimal use of this machine. It can be installed by the partner. Furthermore, the machine technology can be distributed to similar industries.Key words: polishing machine, for silver,